Pengenalan Budidaya Tanaman Hidroponik Sederhana Sistem Sumbu (Wick System) Untuk Anak SD Kelas IV & V - Anggun Nur Mustikawati; Della Novitasari; Febriana Nur Cahyaningrum; Putri Dwi Agustina; Sagita Alfitasya Maghfiroh; Indra Dwi Febryanto (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Nowadays, agricultural development and appropriate agricultural techniques are becoming more and more diverse. Agricultural development can only be achieved through education, and this development must be recognized as an agricultural innovation. The wick hydroponic system, which can be done by anyone, is an agricultural innovation to be introduced. Fourth and fifth grade students attended the activities at SDN Tambakrejo 2. Exposure, practice, and questions used. Students were asked to plant and care for hydroponic plants such as pakcoy, green salad, caisim, and green salads. Questions and answers show the interest and enthusiasm of students in agriculture.